Use of Imported Inputs and the Cost of Importing : Evidence from Developing Countries - Amin, Mohammad (Taylor and Francis, 2014)
For a representative sample of manufacturing firms in 26 countries, the article shows that changes in the cost of importing over time is significantly and negatively correlated with changes in the percentage of firm’s material inputs that are of foreign origin. Furthermore, we show that there may be a non-linear relationship between import costs and imports. These findings are important as recent studies point towards a significant positive effect of imported inputs on productivity and growth. We hope that the present article inspires more work on the determinants of imported input usage especially in developing countries.